H.M. Rasjidi's View on The Modern Western Civilization - Mohammad Zakki Azani (Universitas Darussalam Gontor, 2021)
This study aims to discuss the development of Western thought and civilization according to H. M. Rasjidi by revealing its characteristics. This research is qualitative, with descriptive and analytic methods. The results found that modern Western civilization cannot be separated from the thoughts and reflections of their philosophers about the nature of life and the universe as well as their experiences in viewing the history of religion in the West. The system of the theocracy of the church has triggered the emergence of secularism which moves freely from the domination of church doctrine. This understanding was formed from rationalism, the Protestant movement, and humanism. It was from those processes of thought that the West can develop. So today they reject the spiritual values of religion. In the end, religion is undermined and only becomes a private matter. Religion is separated from state affairs, science, morality and serves only as ceremonial matters, such as; a ritual of birth, marriage, and death. In addition, Rasjidi argues that the West rejects absolute truth even though it comes from God. This Western view of life has become one of Rasjidi's special concerns because it has a direct or indirect effect on the lives of Muslims, especially in Indonesia.